Amine Exchange Reactions of Bis(isonitroso-b-ketoimino) Nickel(II) Complexes with Polyamines and Thiosemicarbazide - Balasubramanian, V.; Muthukumaran, S.; Rosekumari, I.; Lilly, K.O.; Ravi, A. (Asian Journal of Chemistry, 2016)
Amine-exchange reactions on Ni(II) complexes of bidentate oximino-b-ketoimines are investigated. With diethylene triamine and tetraethylene pentamine, both the –NH2 ends of polyamines undergo amine-exchange with the imine –NH protons of the parent complexes. In the case of thiosemicarbazide, it is found that only the imine –NH proton of 5-membered ring undergoes amine exchange. The structures of the amine exchange reaction products have been discussed based on the spectroscopic results.